Noise Reduction in ECG Signals Using Notch Filter - Saxena, Chhavi; Murarka, PD; Kumar Gupta, Hemant (International Journal of Computer Sciences and Engineering, 2025)
Heart problems are increasing frequently day by day and ECG reflects the activities and the attributes of the human heart. The information extracted from the signal is used for analysis and identifying various pathological conditions, but these ECG signal can be distorted with noise as Electrocardiogram (ECG) signals are the electrical recording of heart activity. These signals are very low frequency signals of about 0.5Hz -100Hz. Noise can be any interference due to motion artifacts or due to power equipment that are present where ECG had been taken. A typical computer based ECG analysis system includes a signal pre-processing, beats detection and feature extraction stages, followed by classification. Automatic identification of arrhythmias from the ECG is one important biomedical application of pattern recognition. Moreover ECG signal processing has become a prevalent and effective tool for research and clinical practices. This paper focuses on ECG signal processing using Notch Filter for biomedical application.